1995
DOI: 10.1007/bf00373887
|View full text |Cite
|
Sign up to set email alerts
|

Optical multisite monitoring of cell excitation phenomena in isolated cardiomyocytes

Abstract: An especially designed setup which consists of an inverted fluorescence microscope, an argon ion laser and a photodiode array system permits membrane potential monitoring in isolated guinea-pig ventricular cardiomyocytes, stained with the voltage-sensitive dye di-4-ANEPPS, which responds linearly with relative fluorescence changes (delta F/F) approximately -8% per 100 mV. About a dozen measuring spots covering a single cell were simultaneously monitored with a spatial and temporal resolution of 15 microns and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0
5

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 39 publications
6
36
0
5
Order By: Relevance
“…Highresolution optical mapping of voltage-dependent changes in cardiac tissue [21][22][23] has previously been used in the adult mouse, 24,25 the embryonic chick, 26,27 and other rodent hearts, 26 as well as cellular preparations. 28,29 This study uses optical mapping to explore the role of Cx43 in cardiac impulse propagation during the embryonic development and the early postnatal life in the mouse.…”
mentioning
confidence: 99%
“…Highresolution optical mapping of voltage-dependent changes in cardiac tissue [21][22][23] has previously been used in the adult mouse, 24,25 the embryonic chick, 26,27 and other rodent hearts, 26 as well as cellular preparations. 28,29 This study uses optical mapping to explore the role of Cx43 in cardiac impulse propagation during the embryonic development and the early postnatal life in the mouse.…”
mentioning
confidence: 99%
“…When V m in the depolarized section of the cell reaches the activation threshold, a sufficient number of ion channels are opened to initiate an action potential, which then spreads into the entire cell. These predictions about the distribution of shock-induced V m changes and activation pattern were confirmed on a qualitative level in measurements from isolated cardiac myocytes using fluorescent V m -sensitive dyes and optical mapping techniques (11)(12)(13).…”
Section: Cellular Mechanisms Of Defibrillation Single Cell V M Responmentioning
confidence: 59%
“…The two methods of stimulation are fundamentally different. A current injection triggers a uniform depolarization, whereas an electric field will expose each part of the membrane to different potentials during stimulation (8,22,31,41,47,48). We observed that contraction characteristics depend on the stimulation method used.…”
mentioning
confidence: 84%
“…What can the reason be for this? When a cell is stimulated by a uniform electric field and aligned parallel to it, the two ends are nonuniformly (and oppositely) polarized, and different regions of the cell experience very different transmembrane voltages (8,22,31,33,41,47,48). Spatial differences have also been observed in the intracellular Ca 2ϩ ([Ca 2ϩ ] i ) transient (7,32).…”
Section: Field Stimulationmentioning
confidence: 99%
See 1 more Smart Citation